Analisis Stabilitas Lereng Pada Kegiatan Galian Clay Pada Tambang IUP OP Jumaidi, Kelurahan Gunung Sarik, Kecamatan Kuranji, Kota Padang, Sumatera Barat - Muhammad Reyhand; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2022)
IUP OP Jumaidi is one of the mining business licenses engaged in mining, especially clay mining and trading, which is located in Gunung Sarik Village, Kuranji District, Padang City, West Sumatra Province. Based on field observations at the IUP OP Jumaidi, the authors found that there are manufactured slopes or former mining slopes consisting of slope-forming material, namely clay, with a slope geometry of 44 meters high and a slope of 45o. The existence of mining activities, such as excavation, and transportation of material on the slopes forms the final slope (ex-mining slope) whose stability is not yet known, so it is feared that there will be a landslide hazard. The collapse of the slope in the horizontal plane adjacent to the access to the mining deposit area in 2022 could disrupt mining activities in the IUP OP Jumaidi. The method used in this study is the Bioshop Simplified with a standard safety value of > 1.3. The results of testing the physical properties and mechanical properties of the slopes are the natural bulk density of 16.33 kN/m3, the dry bulk weight of 12.45 kN/m3 and the saturated weight of 17.25 kN/m3. Meanwhile, the cohesion value is 41,256 kN/m3 and the internal shear angle is 25,09o. Based on the parameter values of the physical and mechanical properties of soil in the laboratory, the safety factor value according to the Bioshop Simplified in natural conditions is 1.027, while the safety factor value of the Hoek and Bray in dry conditions is 1.17 and for saturation condition of 0.93. The results showed that the FK value obtained a single slope geometry recommendation with a slope of 35o with a safety factor (FK) of 1.377 in natural conditions according to the bioshop. While the value of the safety factor (FK) in the saturated condition is 1.350. And the double slope according to the Bishop method, the factor of safety (FK) in the natural state is 1.341, and the value of the safety factor (FK) in the saturated condition is 1,309.recommended to use a double slope slope with a bench width of 16 meters and a slope of 39o. The volume to be peeled is 29034.79 bcm.